Ole Boy: [Memoirs of Labour Leader J.K. Bell] - Calhoun, Sue (Nimbus, 1992)
J.K. Bell was one of the finest labour leaders of his time. Born in Halifax, Nova Scotia at the turn of the century, Jimmy Bell headed down the proverbial road to Toronto to find work as the depression years began. When war broke out, he returned to Saint John, New Brunswick and went to work at the dry dock where he founded a local of what would become the Maritime Marine Workers' Federation. For many years, Bell was ostracized by the labour movement because of his leftwing views. As the Cold War whipped the country into hysteria, Bell was "purged" from the provincial labour federation in 1949, and didn't succeed in being re-elected until 1965. Nonetheless, he managed to play a key role, and in this book, he remembers the events and recalls the characters with fondness and humour. --Publisher's description
Keywords: Bell, J. K. (James Koval); Biography; Nova Scotia; Officials and employees; Trade unions